Intellectual property and quality of education: Exploring the academic integrity among medical students - Beketov, Vladimir; Lebedeva, Marina (Frontiers in Education, 2022)
This paper offers an innovative course for building and improving knowledge on plagiarism. The tasks were as follows: (1) analyze existing knowledge about intellectual property and plagiarism among medical students before and after taking the special course; (2) examine the causes affecting students' intellectual property infringement. To assess the awareness of academic integrity and plagiarism among medical students, the author’s questionnaire was used. The sample consisted of 658 students who were divided into two groups. The mean age was 22.41±0.63 years (group 1) and 26.31±0.83 years (group 2). In order to raise awareness of intellectual property and plagiarism, Intellectual Property in Medicine course was offered. The level of duplicate publication and compilation fell. The number of students who believe plagiarism is a moral issue increased. Plagiarism is mostly caused by: large scale digitization; lack of special knowledge; the status value of academic titles; low pay. The research findings make it possible to integrate courses on intellectual property and plagiarism into higher education, which will improve knowledge and high quality of education. There are also plans to introduce an online course in The Unified Anti-Plagiarism Principles in Higher Education for university students to improve knowledge and skills in dealing with aspects of plagiarism.